(untitled) (Comprehensive Journal of Science, 2025)
This study addresses the topic of Islamic advice (alnasihah) and its role in promoting societal peace, in light of the research problem concerning the function of Islamic advice according to the objectives of Sharia in achieving social security and stability. It focuses on five main questions related to the concept of advice and its regulations, the concept of societal peace, the realization of Sharia objectives through advice, and its jurisprudential applications in conflict resolution. The study comprises two main sections. The first section discusses the Jurisprudential Foundation of Advice, which includes three subsections: the first presents the concept and legitimacy of advice; the second outlines its rules and etiquette; and the third illustrates the role of advice in achieving the general and specific objectives of Sharia. The second section deals with Societal Peace and the Role of Advice in Preserving It, comprising three subsections: the first explains the concept and legitimacy of societal peace; the second reviews the manifestations and consequences of its disruption; and the third demonstrates the impact of advice in preserving social peace and achieving Sharia objectives. The study relies on the inductive method to analyze Sharia texts and jurists’ opinions, as well as the descriptive - analytical method to present concepts and link them to reality, emphasizing that advice is a preventive and corrective tool for enhancing social security and cohesion.